Kepentingan Zikir dalam Mendidik Rohani dan Jasmani Pendakwah - Hj. Syed Hussin, Syed Abdurahman bin (Jurnal Usuluddin, 1998)
The article elaborates the significance of zikr in generating spiritual and physical strength of the da'i.